AB0133 Expression of pro-resolving specialised mediators' receptors in rheumatoid arthritis. (12th June 2018) - Perniola, S.; Dinoia, L.; Lacarpia, N.; Natuzzi, D.; Bizzoca, R.; Iannone, F.
Abstract : Background: Inflammation is the physiologic response against noxious stimuli to restore homeostasis and tissue repair. At the initial phase, characterised by an increase in pro-inflammatory cytokines aiming to neutralise the tissue injury, the resolution process must follow to down-regulate the inflammation and to promote the tissue repair. That latter phase is driven by the so called Pro-Resolving Specialised Mediators (SPMs), such as Resolvin (RvD and RvE), Protectins, Maresins and Lipoxin A4 (LXA4), bioactive metabolites of omega-3 fatty acids that act by interacting with specific cellular receptors: CMKLR1 and BLT1 for RvE1, FPR2 and GPR32 for RvD1 and FPR2 for LXA4. In rheumatoid arthritis (RA) the reactive inflammation becomes persistent and the innate immune response turns into the adaptive immune activation. Nowadays there is no evidence whether SPMs are involved in RA pathogenesis. Objectives: Purpose of this study was to evaluate the expression of CMKLR1, FPR2 and BLT1 in RA patients and to correlate it to the disease activity. Methods: Patients affected with RA, according to the 2010 EULAR/ACR classification criteria, were enrolled in this study. Exclusion criteria were: minority age, status of pregnancy or breastfeeding, concomitant any other autoimmune disease. At entry, ESR, CRP, DAS28-ESR, CDAI, Health Assessment Questionnaire Disability Index (HAQ) and peripheral venous blood sample were collected. Based on DAS28-ESR, patients were divided into high-moderate (H-Mo/RA if DAS28-ESR≥3.2) and low-remission (L-Rem/RA if DAS28 <3.2) disease activity group. The expression of CMKLR1, FPR2 and BLT1 in peripheral T cells (CD3) and monocytes (CD14) was evaluated by flow-cytometry assay. Differences for continuous variables were evaluated using the Mann-Whitney test, while for categorical data the Fisher's probability test. Correlations were assessed using the Spearman test. Results: Thirty RA patients, 21 H-Mo/RA and 9 L-Rem/RA, were studied. While no difference in the expression of CMKLR1, FPR2 and BLT1 in CD3-T cells between the 2 groups was found, SPMs receptors were differently expressed on CD14-monocytes. BLT1 + CD14 + cells were significantly higher in L-Rem/RA (90, 96%) than in H-Mo/RA/RA (56, 70%) (p: 0.0001). Likewise, FPR2 + CD14 + cells were significantly higher in L-Rem/RA (92, 29%) than in H-Mo/RA/RA (79, 94%) (p: 0.01). CMKLR1 expression in monocytes was not regulated by disease activity. We also demonstrated an inverse correlation between BLT1 level in monocytes and ESR (p: 0.01), CRP levels (p: 0.008), DAS28-ESR (p: 0.03), CDAI (p: 0, 0076) and HAQ (p: 0, 0138) and a weak correlation between FPR2 expression and HAQ (p: 0.05) (figure 1). ESR: Erythrocyte Sedimentation Rate; CRP: C-Reactive Protein; DAS28-ESR: Disease Activity Score of 28 joints; CDAI: Clinical Disease Activity Index; HAQ: Health Assessment Questionnaire Disability Index. P-value<0.05 was considered statistically significant. Conclusions: In this study, FPR2 and BLT1 expression seem to be regulated by the activity of RA disease. As FPR2 and BLT1 should be involved in down-regulating the inflammation by monocytes, it might be hypothesised that a defective signalling through these SPMs receptors may contribute to sustain chronic inflammation in active RA. However, further studies are needed to explore the intrigue mechanisms beyond inflammation and its resolution. References: [1] Serhan CN. Pro-resolving lipid mediators are leads for resolution physiology. Nature2014Jun 5. [2] Serhan CN, et al. Endogenous pro-resolving and anti-inflammatory lipid mediators: a new pharmacologic genus. Br J Pharmacol2008Mar. Disclosure of Interest: None declared